Antidepressant-Like Effects of Acupuncture-Insights From DNA Methylation and Histone Modifications of Brain-Derived Neurotrophic Factor - Jiang, Huili; Zhang, Xuhui; Lu, Jun; Meng, Hong; Sun, Yang; Yang, Xinjing; Zhao, Bingcong; Bao, Tuya (Frontiers in Psychiatry, 2018)
Sensitive and stable biomarkers that facilitate depression detection and monitor the antidepressant efficiency are currently unavailable. Thus, the objective is to investigate the potential of DNA methylation and histone modifications of brain-derived neurotrophic factor (BDNF) in monitoring severity and antidepressive effects of acupuncture. The depression rat model was imitated by social isolation and chronic unpredicted mild stress (CUMS). The expression of serum BDNF was detected by enzyme-linked immunosorbent assay (ELISA), the hippocampal BDNF, acetylation levels in histone H3 lysine 9 (acH3K9), and HDAC2 by Western blot, the hippocampal mRNA of BDNF by RT-polymerase chain reaction (PCR). The DNA methylation patterns of the promoter I of BDNF was detected by MS-PCR. We investigated that the expression of BDNF in serum and hippocampus were significantly downregulated compared with controls. The same trend was found in mRNA of BDNF. Notably, acupuncture reversed the downregulation of BDNF in serum and hippocampus and mRNA of BDNF compared with model group. Acupuncture reversed the CUMS-induced downregulation of hippocampal acH3K9. On the contrary, the CUMS-induced upregulation of hippocampal HDAC2 in model group was significantly reversed by acupuncture. Collectively, the antidepressant effect of acupuncture might be mediated by regulating the DNA methylation and histone modifications of BDNF, which may represent novel biomaker for detection of depression and monitoring severity and antidepressive effects.